2015
DOI: 10.1007/s00221-015-4300-2
|View full text |Cite
|
Sign up to set email alerts
|

The plausibility of visual information for hand ownership modulates multisensory synchrony perception

Abstract: We are frequently changing the position of our bodies and body parts within complex environments. How does the brain keep track of one's own body? Current models of body ownership state that visual body ownership cues such as viewed object form and orientation are combined with multisensory information to correctly identify one's own body, estimate its current location and evoke an experience of body ownership. Within this framework, it may be possible that the brain relies on a separate perceptual analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
1
9
1
Order By: Relevance
“…Second, in contrast to our present finding, it has been shown that participants detected a false visual feedback already at quite brief delays (e.g., </ = 150 ms) [ 8 , 9 , 28 , 47 , 48 ]. In contrast to these studies that implemented only one kind of feedback (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, in contrast to our present finding, it has been shown that participants detected a false visual feedback already at quite brief delays (e.g., </ = 150 ms) [ 8 , 9 , 28 , 47 , 48 ]. In contrast to these studies that implemented only one kind of feedback (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…We estimated the delay between movement of the hand and visual feedback of its location at approximately 80 ms, using a high-speed camera (120 Hz) camera, by comparing in a test the first frame when the hand moves compared to the first frame when the ellipse moves. This is comparable to the values found in similar setups (Zopf et al, 2015). This delay was not noticeable to the subjects, particularly as subjects could not see their hands moving, only the feedback.…”
Section: Methodssupporting
confidence: 91%
“…the range of movements). Other studies also demonstrated that visual and tactile information from the fake hand and actual unseen hand respectively became less integrated when the fake hand was at an anatomically implausible versus plausible posture 28, 29 . Taken together, these studies indicate that anatomical plausibility of the viewed hand posture plays an important role in multisensory integration 30, 31 .…”
Section: Introductionmentioning
confidence: 98%